Policy Before Technology: Don’t Outkick the Coverage - Lund, Brady (Information Technology and Libraries, 2022)
In the race to adopt the newest and best, practical considerations for emerging technologies are frequently overlooked. Technology can set an organization apart and, in the case of libraries, be instrumental in helping demonstrate value. Yet, all new technologies carry additional, potentially unpleasant consequences, whether it be threats to privacy and security, barriers to accessibility or risks to health, learning barriers, or exposure to misinformation. Organizations must consider these threats before introducing new technologies, rather than the other way around. To illustrate these threats and their policy implications, I will briefly discuss two popular technologies/innovations—virtual reality and data analytics—and the threats that are often overlooked by organizations and how they may be appropriately addressed by policy.